PENGELOLAAN PENDIDIKAN LINGKUNGAN BERBASIS PESANTREN - Rihlah Nur Aulia; Izzatul Mardhiah; Dian Bagus; Ade Gunawan; Dian Elvira Nanda Sari (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2018)
This research is backgrounded by some environmental problems which increasingly worries day plus the problem of management of natural resources that are not friendly and tend to be greedy. The rapid pace of development and population growth in the past decade has led to the conversion of forest and agricultural land into industrial, plantation and residential areas, resulting in degradation of uncontrolled environmental damage and pollution. The main purpose of this research is to know how environmental management conducted by Pondok Pesantren SPMAA Lamongan, East Java. In addition, the purpose of this study to find out how the implementation of environmental management conducted by the boarding school as a mirror of concern for the surrounding environment. This research uses qualitative approach. This means that the data collected is not a number, but the data comes from interviews, personal documents, memo notes, field notes, and other official documents. So that the purpose of this study is to describe the empiric reality behind the phenomenon in depth, detailed, and thorough. This research concludes that every pesantren has its own characteristic in running the concept of ekopesantren that exist, and in this pesantrenen pesantren SPMAA ekopesantren understood as pesantren that can coexist with nature and full of lesson will utilize resources wisely and wisely. Although this boarding school has not fully implemented ekopesantren. This is seen from ecopesantren indicator that has been fulfilled and that has not been fulfilled.